SUCCESSFUL INVESTMENT AND ITS RESULT (BASED ON PERSONAL EXPERIENCE) - Alireza Pandkhai (Scholar Express Journals, 2023)
This article highlights the achievements of a young leader and millionaire based on his personal experience. The paths to success are illuminated. Also given suggestions based on his experience
Keywords: business; investment; entrepreneurship